Komunikasi Pemasaran dalam Meningkatkan Kunjungan Wisatawan: Studi Kasus Wisata Jasmineparkind Kab. Tangerang - Kusumawardani, Frisca; Mochammad Mirza; Ajeng Pradesti (Economic Reviews Journal, 2024)
Marketing communication is a means by which companies inform, persuade and increase consumers directly or indirectly about the products, brands or services they sell. The aim of this research was to determine the marketing communications carried out by Jasminepark in increasing tourist visits and the obstacles and supporters in increasing tourist visits. This research uses the IMC (Integrated Marketing Communication) theory with 5 elements, namely advertising, sales promotion, public relations, personal selling, and direct marketing. This research used a descriptive qualitative method by interviewing 5 informants, namely, Jasminepark marketing, Jasminepark Supervisor, and 3 visitors. Data collection techniques used in research are interviews, observation and documentation. The results of this research show that Jasminepark's marketing communications in increasing tourist visits use Integrated Marketing Communication (IMC). This increases the number of tourist visits to Jasmineparkind.